2020
DOI: 10.3390/cancers12092693
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-Related Protein 1 as a Biomarker against Incomplete Age-Related Lobular Involution and Microcalcifications’ Development

Abstract: As a downregulator of the Wnt signaling pathway, SFRP1 is involved in several components of the age-related lobular involution process such as inflammation, apoptosis, and adipogenesis. Because microcalcifications are associated with inflammation, we aimed to demystify the cross talk between SFRP1, inflammatory markers, and microcalcifications by assessing SFRP1 expression (immunohistochemistry) in a cohort of 162 women with different degrees of lobular involution. SFRP1 expression was inversely associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…TMAs were constructed from the FFPE mastectomy blocks containing BC tissue samples as previously described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…TMAs were constructed from the FFPE mastectomy blocks containing BC tissue samples as previously described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, by activating the Wnt signaling pathway, they also observed a decrease of bone resorption combined with an induction of osteoblast mineralization [ 30 ]. In breast, SFRP1 expression is higher during age-related lobular involution and in presence of microcalcifications compared with patients completely involuted and without microcalcification, respectively [ 90 ]. Interestingly, the incidence of RA in breast cancer patients is lower compared with patients without breast cancer after adjustment for age, comorbidities and breast cancer treatments [ 31 ].…”
Section: Overview Of the Most Frequent Osteoimmunological Disordermentioning
confidence: 99%
“…SFRP1 is a good predictor of the degree of lobular involution and its expression is higher in presence of microcalcifications. Moreover, SFRP1 expression is lower in involuted nulliparous women compared with involuted non-nulliparous women suggesting that the first lobular involution is different from the others [ 90 ]. This is particularly important to consider as lower expression of SFRP1 in breast tissue is largely associated with breast cancer development and poor prognosis [ 134 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ].…”
Section: Osteoimmunology Of the Breast Tissue During A Woman’s Lifmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, our group demonstrated that SFRP1 was largely expressed in non-involuted breast epithelial tissue, while it dramatically decreased after perimenopausal lobular involution completion in nulliparous women. Furthermore, we observed that SFRP1 expression was also associated with the presence of microcalcifications in breast tissue, once more in nulliparous women specifically [ 23 ]. However, in the absence of well-characterized models of lobular involution and microcalcification development in both nulliparous and multiparous mammalians, the knowledge regarding SFRP1 regulation through pregnancy and hydroxyapatite (HA) microcalcifications remains unsubstantial.…”
Section: Introductionmentioning
confidence: 99%